Human migration, diversity and disease association: a convergent role of established and emerging DNA markers - Guha, Pohhraj; Srivastava, Sanjeev K.; Bhattacharjee, Soumen; Chaudhuri, Tapas K. (Frontiers in Genetics, 2013)
With the gradual development of intelligence, human got curious to know his origin and evolutionary background. Historical statements and anthropological findings were his primary tool for solving the puzzles of his own origin, until came the golden era of molecular markers which took no time to prove it’s excellence in unveiling answers to the questions regarding the migration pattern of human across different geographical regions. As a bonus these markers proved very much beneficial in solving criminal offences and in understanding the etiology of many dreaded diseases and to design their prevention. In this review, we have aimed to throw light on some of the promising molecular markers which are very much in application now-a-days for not only understanding the evolutionary background and ancient migratory routes of humans but also in the field of forensics and human health.